Role and Impact relationship between micro finance and poor’s access - A case study of Jaffna District, Sri Lanka. - Yogendrarajah, R.; Semasinghe, D.M. (International Conference on Contemporary Management, (ICCM), Faculty of Management Studies &; Commerce, University of Jaffna., 2014)
Microfinance has become a vital role in access to poor people in the rural areas. It assists the poor people in health nutrition, education and self employment opportunity etc. The major objective of this study is to show the relationship between role & impact of Micro finance on Poor peoples’ access in the study area. This study is based on both quantitative and qualitative methodologies in order to find out the possible solution of the problem. The study was guided by the following research questions: what are the problems relating to access of microfinance? And the mechanism for obtaining the micro finance? To what extent the problems enabled the respondents to get the micro finance services? Stratified random sampling techniques were used to get a total of 106 respondents. Data were collected through close ended questionnaires, semi structured interviews, discussions, observations and documentary reviews. Data analysis was based on descriptive statistics using various statistical tools like regression, correlation, t- test and ANNOVA by using SPSS package. The Study findings show that the majority of the poor have access to micro finance because they have affected by the war. In the Post war context the micro finance assistance is important to those people. However some respondents have also indicated that micro finance does not make them successful in their undertakings as they make them to become more dependants on them. Micro financial institutions should encourage poor to borrow by revisiting the collateral conditions and reducing interest rates. The result of the study was that microfinance helps the different categories of poor people and has the positive significant effects on the dependent variable i.e access to micro finance. It was found that there is a high interest rate on micro loans because of the administrative cost. The government takes interest and supports the microfinance sector. The results of the study also show that there is improvement in access of the microfinance in the recent times in terms of investments, active borrowers, branches and personnel etc because of the rehabilitation of the war affected areas in Sri Lanka.
Keywords: Micro finance; Poverty; Living standard; Self Employment; Health care